Optimizing Livestock Nutrition Through Mineral Supplementation: Empowering Cendana Farmer Group in Pesisir Selatan, West Sumatera - Tinda Afriani; Yurnalis Yurnalis; Reswati Reswati; Adisti Rastosari; Mylaufa Asyraf (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The community service program aims to improve the productivity of cattle farming in the Cendana farmer group in Pesisir Selatan Regency, West Sumatra. The program focuses on raising awareness about the importance of providing minerals as a crucial component of animal feed. Minerals such as calcium, phosphorus, and magnesium play a significant role in the growth and health of cattle. The program results reflect an improvement in farmers' understanding of the role of minerals in animal nutrition. It is expected that they will be able to enhance cattle productivity by ensuring the fulfillment of mineral requirements in their feed. This program has the potential to support sustainable farming efforts by preventing mineral deficiencies in cattle. The training imparted theoretical knowledge and taught proper mineral selection, correct dosages, and cattle's health and productivity benefits. This program encourages livestock owners to apply their newfound knowledge in their day-to-day farming practices. This community service program has the potential to significantly improve the quality and well-being of farmers in the region and support the overall growth of the livestock sector.